NATIVE SPEAKER – NON-NATIVE SPEAKER INTERACTION: THE USE OF DISCOURSE MARKERS - Iglesias Moreno, Ángela Eugenia (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Discourse markers have a basic role in oral interactions. Apart from providing coherence and regulating turn-taking, they have important interactive functions that indicate the conversational commitment and the social behaviour of the interlocutors in an interaction. In the case of the L1, discourse markers are acquired as part of our communicative competence, and, therefore, it is important that they also be part of an L2 student’s communicative competence. In this article, I will analyse the use of “well” as a discourse marker (DM) by Spanish students of English in interaction with native speakers. The analysis will indicate that “well” is hardly used as a DM in the students’ discourse, resulting in distinctly non-native discourse, which can negatively affect the students’ images. These results may be significant to teachers and researchers in regard to their approach to the teaching of foreign languages from a pragmatic point of view.